Constructing multifunctional heterostructure of Fe2O3@Ni3Se4 nanotubes - Zheng, Penglun (2020)
Heterostructures have attracted increasing attention due to their amazing synergetic effects, which may improve the electrochemical properties, such as good electrical/ionic conductivity, electrochemical activity, and mechanical stability. Herein, novel hierarchical Fe2 O3 @Ni3 Se4 nanotubes are successfully fabricated by a multistep strategy. The nanotubes show length sizes of ≈250-500 nm, diameter sizes of ≈100-150 nm, and wall thicknesses of ≈10 nm. The as-prepared Fe2 O3 @Ni3 Se4 nanotubes with INi:Fe = 1:10 show excellent Li storage properties (897 mAh g-1 high reversible charge capacity at 0.1 A g-1 ), good rate performance (440 mAh g-1 at 5 A g-1 ), and outstanding long-term cycling performance (440 mAh g-1 at 5 A g-1 during the 300th cycle) as an anode material for lithium ion batteries. In addition, the Fe2 O3 @Ni3 Se4 nanotubes with INi:Fe = 1:10 (the atomic ratio between Ni and Fe) show superior electrocatalytic performance toward the oxygen evolution reaction with an overpotential of only 246 mV at 10 mA cm-2 and a low Tafel slope of 51 mV dec-1 in 1 m KOH solution.